Biotechnologie und Militär: Perspektiven des Biowaffen-Verbots - Hunger, Iris (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
All major technologies have been exploited not just for peaceful, but also for hostile purposes. Biotechnology constitutes an exception. At the time when the biotech revolution began in the early 1970s, states agreed to ban biological weapons from their arsenals. This ban, however, has been weakened over the last 15 years. This article describes this process and the efforts to reverse it.